MENGURAI MODEL KESEJAHTERAAN PETANI - Paranata, Ade; Wahyunadi, W; Daeng, Akung; Wijimulawiani, Baiq Saripta (Semarang State University, 2012)
This research aims to determine the relationship between latent variables such as climate, infrastructur, social, economic, policy, institution, technical production and the production of rice farmers. The research locations are 10 districts in Sumbawa and the respondents are 239 farmers.This research is a correlaÂtional research that connects two or more variables. The research uses quantitative data. Descriptive statistical analysis and multivariate analysis are used to analize the data. The statistical analysis consists of cross tabulation and chi- square. The cross tabulation is used to test significant using chi-square analysis. Chi-square analysis is used to examine the relationship (association) between several independent variables and the variable of welfare. The multivariate analysis used is Structural Equation Modelling. SEMis used for the study because some variables are unobservable and reciprocal (recursive).The results of study shows that the simultaneous connection of latent variables affects the production of latent variables and the production variables influence the welfare variable.Tujuan dari penelitian ini adalah untuk menentukan hubungan antara variabel-variabel yang tersemÂbunyi seperti iklim, infrastruktur, sosial, ekonomi, kebijakan, kelembagaan, teknis produksi benih dan produksi petani padi. Lokasi dari penelitian ini adalah 10 daerah di Sumbawa dan respondennya adalah 239 petani. Penelitian ini merupakan penelitian korelasi yang menghubungkan dua atau lebih variabel. Penelitian ini menggunakan data kuantitatif. Analisis statistik deskriptif dan multivariat juga digunakan untuk menganalisis data. Analisis statistik terdiri dari analisis tabel silang dan chi-square. Analisis chi-square digunakan untuk melihat hubungan (asosiasi) antara beberapa variabel independen dengan kesejahteraan. SEM digunakan karena variabel penelitian diantaranya bersifat unobservable dan bersifat resiprokal (recursive). Hasil penelitian ini menunjukkan bahwa hubungan antar varibel yang berlangsung secara simultan mempengaruhi produksi variabel-variabel laten, dan variabel produksi mempengaruhu variabel kesejahteraan.